Epidemiological Characteristics of Lung Cancer Incidence in the Tumor Registration Area of Gansu Province from 2010 to 2019 - Zhaoxia LU; Jixiong MA; Juhong MA; Hong ZHOU; Juanjuan XUE; Gaoheng DING; Yindi WANG; Zhen LV; Yuqin LIU; Ben WANG; Lili CHEN (Chinese Journal of Lung Cancer, 2024)
Background and objective Lung cancer is the malignant tumor with the highest incidence rate and the heaviest disease burden in China. In recent years, lung cancer has shown a high incidence trend, seriously affecting the health of the population. In this paper, we analyze the characteristics of lung cancer incidence in 2019 and the trend of incidence rate from 2010-2019 in the tumor registration area of Gansu province, in order to provide a reference basis for the development of lung cancer prevention and control strategies in Gansu province. Methods By analyzing the cases of lung cancer incidence in the tumor registration area of Gansu province in 2019, we calculated the incidence rate, medium incidence rate, world incidence rate and other related indexes; we used Joinpoint to calculate the annual percentage change (APC) for trend analysis. Results In 2019, a total of 3757 new cases of lung cancer were reported in Gansu province, accounting for 14.96% of all new malignant tumors. The incidence rate, medium incidence rate and world incidence rate and world rate of lung cancer were 40.52/105, 25.78/105, 25.86/105; and the cumulative rate of 0-74 years old, and the truncation rate of 35-64 years old were 3.23%, 40.03/105, respectively. The incidence of lung cancer rises with age, and is high in the age group of 40 years and above, and the incidence peaks in the male and female populations in the group of 75 years and above, and the group of 80 years and above, respectively. The crude incidence rate of lung cancer in the tumor registration area of Gansu province from 2010-2019 showed an overall increasing trend, and the rate of increase was relatively fast, with an APC 5.39% (P<0.05); Separately, according to gender, urban and rural areas, the incidence of lung cancer in all populations showed an increasing trend, and the APC of male, female, urban and rural populations were 4.98%, 6.39%, 6.26%, and 4.64%, respectively (all P<0.05). According to the trend analysis of lung cancer incidence rate by age group, only lung cancer incidence in the age group of 65 years and above increased at an annual average rate of 4.15% (P<0.05). Conclusion The incidence rate of lung cancer in the tumor registration area of Gansu province from 2010 to 2019 shows a rising trend year by year, and there are differences in the incidence of lung cancer in people of different genders, regions and age groups, so comprehensive prevention and control work should be carried out for the key populations of lung cancer incidence.